Conductive Passivator for Efficient Monolithic Perovskite/Silicon Tandem Solar Cell on Commercially Textured Silicon. Issue 46 (26th October 2022) - Xu, Qiaojing; Shi, Biao; Li, Yucheng; Yan, Lingling; Duan, Weiyuan; Li, Yuxiang; Li, Renjie; Ren, Ningyu; Han, Wei; Liu, Jingjing; Huang, Qian; Zhang, Dekun; et al.
Abstract: Monolithic perovskite/silicon tandem solar cells on commercially textured silicon with conformal perovskite top cells allow compatibility with standard industrial processes of silicon photovoltaic, as well as maximization of light trapping at the least cost. However, the efficiency is still limited by unsatisfactory open‐circuit voltage ( V OC ) and fill factor (FF), owing to the challenge of growing high‐quality perovskite film on textured substrates and the lack of particularly effective passivation at the inferior interface between perovskite and C60 . Different from traditionally electricity‐insulating passivator, herein, a conductive organic amine salt is introduced into this interface to suppress nonradiative recombination loss and promote carriers transfer synchronously, significantly increasing the V OC while preserving high FF, thus improving the efficiency substantially. Finally, a champion efficiency of up to 28.51% is obtained. Furthermore, due to the favorable electrical properties of this molecule, there is a wide processing window for the passivation, which helps to achieve an efficiency of 25.13% when the active area is enlarged to 11.879 cm 2 . Abstract : Conductive passivation strategy is proposed to address one of the key issues of non‐ideal open‐circuit voltage and fill factor in industry‐compatible, fully textured perovskite/silicon tandem solar cells. Benefitting from the better electrical property, favorable passivation ability, improved interface charge transfer, and wide processing window, efficiencies of 28.51% on 0.5036 cm 2 and 25.13% on 11.879 cm 2 are achieved.